2020
DOI: 10.1155/2020/8157858
|View full text |Cite
|
Sign up to set email alerts
|

Combined Aerobic and Resistance Exercises Evokes Longer Reductions on Ambulatory Blood Pressure in Resistant Hypertension: A Randomized Crossover Trial

Abstract: Aim. The present study compared the acute effects of aerobic (AER), resistance (RES), and combined (COM) exercises on blood pressure (BP) levels in people with resistant hypertension (RH) and nonresistant hypertension (NON-RH). Methods. Twenty patients (10 RH and 10 NON-RH) were recruited and randomly performed three exercise sessions and a control session. Ambulatory BP was monitored over 24 hours after each experimental session. Results. Significant reductions on ambulatory BP were found in people with RH af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 57 publications
(96 reference statements)
1
21
0
Order By: Relevance
“…Ten studies ( N = 380 participants, 51% female , age range 52 to 67 years) were included in the review, of which four ( 15 , 16 , 27 , 28 ) ( N = 58, 50% female) assessed the short-term (≤ 24 h) effects of acute physical exercise and six ( 17 , 18 , 20 , 29 31 ) ( N = 322, 51% female) assessed the mid-term (up to 6 months) effects of exercise training intervention ( Table 1 , Flowchart available as Supplementary Figure 1 ). Participants of two studies ( 19 , 32 ) were enrolled in a larger RCT ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies ( N = 380 participants, 51% female , age range 52 to 67 years) were included in the review, of which four ( 15 , 16 , 27 , 28 ) ( N = 58, 50% female) assessed the short-term (≤ 24 h) effects of acute physical exercise and six ( 17 , 18 , 20 , 29 31 ) ( N = 322, 51% female) assessed the mid-term (up to 6 months) effects of exercise training intervention ( Table 1 , Flowchart available as Supplementary Figure 1 ). Participants of two studies ( 19 , 32 ) were enrolled in a larger RCT ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…Available evidence on the effects of exercise intervention in individuals with RH shows promising results, as confirmed by some non-systematic reviews ( 11 14 ). Different trials have reported a beneficial effect of acute ( 15 , 16 ) or regular exercise ( 17 20 ) on office BP or ABP in patients with RH. However, to the best of our knowledge there has been no previous attempts to systematically synthesize the evidence available on the effects of acute or regular exercise on BP measures in patients with RH.…”
Section: Introductionmentioning
confidence: 99%
“…Our subjects were not taking anti-hypertensive medications, whereas most studies of PEH in hypertensive individuals have included subjects on blood pressure medications ( Melo et al, 2006 ; Brito et al, 2011 ; Cunha et al, 2016 ; Cunha et al, 2017 ; Ferrari et al, 2017 ; Imazu et al, 2017 ; Cunha et al, 2018 ; Goessler et al, 2018 ; de Freitas Brito et al, 2019 ; Costa et al, 2020 ; Pires et al, 2020 ). Thus, our results may not be applicable to those taking anti-hypertensive medications.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of PEH is positively related to the baseline BP prior to exercise (Brito et al, 2018). Indeed, PEH has been repeatedly demonstrated in hypertensive populations (Legramante et al, 2002;Melo et al, 2006;Brito et al, 2011;Dos Santos et al, 2014;Cunha et al, 2016;Cunha et al, 2017;Ferrari et al, 2017;Imazu et al, 2017;Cunha et al, 2018;Goessler et al, 2018;de Freitas Brito et al, 2019;Pires et al, 2020;Iellamo et al, 2021). However, in virtually all of these studies the hypertensive populations included individuals with and without obesity, with mean BMI < 30 kg/m 2 in most instances.…”
Section: Introductionmentioning
confidence: 99%
“…Physical exercise has been highlighted among the many available alternatives due to evidence supporting the beneficial effects of exercise training programs on BP in NON-RH [ 3 ]. The beneficial effects of physical exercise are not restricted to chronic programs, and low BP levels are also observed after an acute session of exercise, which is called postexercise hypotension [ 4 10 ].…”
Section: Introductionmentioning
confidence: 99%